Evaluation of the quality of cause of death statistics of the last decades in the European Union: Lluís Cirera. (25th October 2022) - Cirera, L; Ballesta, M; Uroz, V; Sameron, D
Abstract: Introduction: The European Union (EU) do not publish the quality of cause-of-death statistics, when is possible to assess quality by reliability. Quality does not present consolidated indicators. Ill-defined and other inaccurate causes have presented different groupings. Objective: To assess the quality of official cause-of-death statistics of the European Union by member states from 2006 to 2020. Methods: Cases and population were from the WHO repertory. We selected causes in EU27 countries by up to fourth code-character of ICD10 -on the EuroStat website were not available-. Case counts were grouped into ill- defined, unspecific, less specific (the latter two, in inaccurate), and judicial (inaccurate external causes) categories, based on literature and expertise. We calculated age-adjusted rates to the Standard European Population by country, sex, period (2006-, 2011- and 2016-2020), and quality category. We tested the Comparative Mortality Ratio (CMR) of each country to the European Union median by a Bayesian approach, at 5% statistical significance. We plotted the rates proportion of each quality category in its all causes. Results: We included 25 countries. Some did not report all years. Six countries showed >19% for ill-defined causes and 3 member states had <5% in both sex and last period. In inaccurate, for the same time period and sex, average pointed 10% with a range of 3-19%. In the same period, CMR exceeded significantly the EU median in 19 and 18 countries for women and men, respectively; and exceeded in unspecific causes in 12 countries for women and men. Discussion: Literature showed that incorrect causes of death were random distributed. Probably major causes were biased and underestimated. Conclusions: Quality of cause of death is a useful indicator of mortality statistics reliability. Quality indicators targeted national gaps across EU. We need a new EU task force on statistics of causes of death in accordance with the XXI century. Key messages:  Quality indicators of causes of death statistics targeted national gaps across the European Union.  The statistics of death causes underestimated the main causes of death in the European Union.